Sinergi Potensi Kuliner Lokal dalam Pengembangan Desa Wisata Pematang Johar, Deli Serdang, Sumatera Utara - Muhammad Zulfan; Ngatemin Ngatemin; Muhammad Rizal Sitepu (JURNAL GASTRONOMI INDONESIA, 2023)
Pematang Johar Village is one of 5 (five) villages in Labuhan Deli District, Deli Serdang that tries to develop its potentials to attract tourists. Some of them are batik (Batik Sawah) which uses natural dyes from mangrove wood waste, making tempeh, various cassava and banana chips and bitter melon chips. Therefore, this study aims to find out the synergy of local culinary potential with the development of tourism villages. Further, it is also to understand what hindrances local culinary to developed in Pematang Johar Tourism Village, to prepare strategies for development of local culinary potential in tourism villages of Pematang Johar, Deli Serdang Regency. The research which was carried out from July to September 2022 is descriptive qualitative research. Data were collected by observation, interviews and questionnaires. The results of the study showed the synergy of local culinary potential with the development of tourist villages and the use of SWOT analysis resulted in strategies to develope culinary potential by looking at the strengths, weaknesses in seeing opportunities and threats to support the development of Pematang tourism villages.